The Harmful Effects of Microplastic Pollution on Aquatic Organisms - Yilmaz, N; Emecan, I T; Elhag, M; Boteva, S; Yilmaz, S M (IOP conference series. Earth and environmental science, 2024)
In recent years, microplastics have been recognized as the most popular pollutants in marine and fresh waters. Plastic is one of the most used materials in all areas of our lives due to its cheap, light, and durable properties. Because they are used as main or auxiliary materials in almost all industries and branches of industry, the disappearance of plastics, which are in our lives, requires very long processes. Since petroleum-derived plastic wastes, which bacteria cannot consume directly, are decomposed by solar heat and radon, only the resulting compounds can be consumed by bacteria. For this reason, awareness-raising efforts to reduce plastic consumption in daily use all over the world have been accelerated. In parallel with this situation, research on microplastic pollution in both seas and inland waters is carried out intensively. Considering the current consumption habits of us humans, who are at the top of the food chain, the rates of microplastics we are exposed to are at a substantial level. The determination of the amount of microplastics contained in seafood consumed as the main protein source is of great importance in terms of public health and shows the necessity of further scientific research on this subject. The purpose of our study is to reveal the effects of microplastic pollution on aquatic organisms both in sea and inland waters by compiling studies on this subject and to draw attention to microplastic pollution in waters.